Green Route Fabrication of Graphene Oxide Reinforced Polymer Composites with Enhanced Mechanical Properties. (13th July 2016) - Mahendran, R.; Sridharan, D.; Santhakumar, K.; Gnanasekaran, G.
Abstract : A facile and "Green" route has been applied to fabricate graphene oxide (GO) reinforced polymer composites utilizing "deionized water" as solvent. The GO was reinforced into water soluble poly(vinyl alcohol) (PVA) and poly-2-acrylamido-2-methyl-1-propanesulfonic acid (PAMPS) matrix by ultrasonication followed by mechanical stirring. The incorporation and dispersion of the GO in the polymer matrix were analyzed by XRD, FE-SEM, AFM, FT-IR, and TGA. Further, the FE-SEM and AFM images revealed that the surface roughness and agglomeration of the GO in the polymer matrix increased by increasing its concentration. Ionic exchange capacity, proton conductivity, and tensile texture results showed that the reinforcement of GO in the polymer matrix enhances the physicochemical properties of the host polymer. These PVA/PAMPS/GO nanocomposites showed improved mechanical stability compared to the pristine polymer, because of strong interfacial interactions within the components and homogeneous dispersion of the GO sheets in the PVA/PAMPS matrix.